Perpaduan inovasi digital dan kerja sama berdaya saing: Perkembangan Usaha Mikro, Kecil, dan Menengah Kota Malang di era konten kreator - Lestari, Anik Ika (Maliki Interdisciplinary Journal, 2024)
Digital innovation encourages the transformation of the economic sector including MSMEs in Malang City. This study analyzes the contribution of digital innovation and competitive cooperation to MSMEs in the creator content era. This study aims to analyze how the adoption of digital innovation and collaboration contribute to the development of MSMEs in Malang City in facing the challenges and opportunities presented by the creator content era. Using a qualitative study with in-depth interviews with MSME owners shows the adoption of innovations such as the use of social media, creative content, and digital marketing. The results of the analysis show that MSMEs in Malang City have taken proactive steps in adopting digital innovation, including utilizing social media platforms, creating creative content, and digital marketing strategies. This innovation provides new opportunities to gain a wider market share, especially through easier access to consumers through digital platforms.